Pengaruh Motif Aplikasi Line Webtoon terhadap Kepuasan Khalayak Membaca Komik Digital - Lina Fardiana Wulandari Faisal; Zulfebriges (UNISBA Press, 2022)
Abstract. Technological advances are running very fast today and play an important role in communication practices. Comics were originally in the form of print media in the form of books. Comics are now starting to change in electronic form and are distributed over the internet. In using the Line Webtoon application, each user has a certain motive to fulfill their satisfaction or needs. The study, entitled